Literary Theory and Creative Writing, a Blended Space For Producing Literary Works - Indah Damayanti (Islamic State Institute of Bengkulu (IAIN) Bengkulu, 2016)
Literary theory is the systematic study of the nature of literature and of the method for analysing literary works. Literary Theory is an examination of a piece of literature which can be addressed to examine a single aspect of the work in its entirety By literary theory we assume not to the meaning of work of literature but to the theories that reveal what literary works can mean. Moreover creative writing focuses on writing from emotions and thoughts which tends to be expressive, imaginative, and literary. Any writing refers to individual expression as a social practice falls to this category. It is believed that creative writing cannot be formed as an acquaintance outside literary theory instead of one that is fashioned within. This paper looks at how creative writing and literary theory should be combined for producing fine-new literary works